Effect of rizobacterias inoculating nitrogen fixers in the cultivation of sweet potato (Ipomoea batatas Lam.) - Lorena Castellanosone, Lily Moon; Sánchez lopez, Diana Beatriz; García Peña, Joaquin Alfonso; Espitia Montes, Amaury Aroldo (MedCrave Publishing, 2024)
The excessive use of nitrogen fertilizers in the nutrition of plants Generates environmental problems and Increases the production costs of crop. Plant Growth Promoting rhizobacteria (PGPR) are an alternative to the use of chemical fertilizers, Favoring the yield of crops. The objective of esta investigation was to determine the effect of inoculation of rhizobacteria With fixed nitrogen sweet potato crop in the Montes de Maria microregion. Sweet potato cutting of the variety Tainung 66, provenance was established under a design of complete blocks at random With an Increased factorial arrangement 3x2+2, with three replications, Where the effect of native strains of Azotobacter sp. (IBCB10) and Azotobacter vinelandii was EVALUATED (IBCB15) mixed With fertilization levels (50% and 75%). The results Obtained Indicate That the inoculation of the IBCB10+IBCB15 bacteria in a mixture With 50% of the nitrogen fertilizer dose, Increased yields the crop by 57% Significantly With respect to the chemical and 93% Control T2 to T1 With relation (Without inoculation). Likewise, the application of the bacterium IBCB10 stimulated the production of dry matter greater tuberous roots of sweet potato, by optimizing the absorption of nitrogen fertilizer reduced to 50%. These results allow to rhizobacteria be included in management alternatives for the mineral nutrition of the sweet potato crop.